Pelatihan Branding dan Packaging Produk UMKM Kue Bolu di Desa Kuok Kabupaten Kampar - El Hadi, Firdaus; Nugraha, Yudhi Martha; Nurjanis (TRIMAS: Jurnal Inovasi dan Pengabdian Kepada Masyarakat, 2024)
Kuok Village in Kampar Regency is famous for its delicious and unique sponge cake production. However, there are still some of them as sponge cake business actors in the village who experience obstacles in terms of branding and product packaging. This makes their products less known and difficult to compete in the market. This service aims to provide branding and packaging training for sponge cake products in Kuok Village, Kampar Regency. The service method used is an experimental approach with pre-test and post-test design. The results of this service show that the branding and packaging training of sponge cake products in Kuok Village, Kampar Regency has proven to be effective in increasing their knowledge, skills, and motivation in branding and packaging products. So that it has an impact on improving the quality of product branding and packaging, which ultimately increases the attractiveness of the product and increases sales results. Thus, it is recommended that branding and packaging training for sponge cake products in Kuok Village, Kampar Regency be carried out continuously with a longer duration. In addition, efforts need to be made to increase access to information about branding and packaging for sponge business actors